2020
DOI: 10.1371/journal.pone.0238678
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential impact of COVID-19 on life expectancy

Abstract: Background The COVID-19 virus pandemic has caused a significant number of deaths worldwide. If the prevalence of the infection continues to grow, this could impact life expectancy. This paper provides first estimates of the potential direct impact of the COVID-19 pandemic on period life expectancy. Methods From the estimates of bias-adjusted age-specific infection fatality rates in Hubei (China) and a range of six prevalence rate assumptions ranging from 1% to 70%, we b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 24 publications
(27 reference statements)
3
65
0
7
Order By: Relevance
“…If the virus continues to spread and mortality reaches 10%, loss in life expectancy is likely to be 1.4 years. Our findings are consistent with literature [ 4 , 8 , 18 ]. A high reduction of life expectancy (2.94 years) has been observed in USA [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…If the virus continues to spread and mortality reaches 10%, loss in life expectancy is likely to be 1.4 years. Our findings are consistent with literature [ 4 , 8 , 18 ]. A high reduction of life expectancy (2.94 years) has been observed in USA [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…A study conducted in Italy found that fatigue, dyspnea, joint pain, and chest pain were persistent among the recovered patients [ 16 ]. Studies have projected premature mortality and reduction in life expectancy due to the infection across countries [ 4 , 8 , 17 , 18 ]. After a certain threshold level of COVID-19 prevalence, life expectancy starts decreasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Petropoulos, a continuation of coronavirus COVID-19 is predicted using a sample. In Muttrack and Scherhov ( 2020 ), the impact of a period of life expectancy is discussed. Forecasting Team Nature ( 2020 ) using the SEIR method predicted COVID-19 patterns and traced the possible outcomes for the period September 22, 2020, to February 28, 2021, using the COVID-19 cases and mortality data from February 1, 2020, to September 21, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The repercussions of COVID-19 pandemic on the global economy and society continue to rise. By 6 January 2021, COVID-19 pandemic had caused more than 20.5 million years of life lost (YLL) due to excess deaths in 81 countries (Arolas et al, 2021) and caused a decline at least a year on life expectancy in many countries (John & Susan, 2020;Marois et al, 2020). Based on the WHO report, the loss of 8.3% in global income, which is attributable to a loss of 8.8% in global working hours as a result of inactivity, rising unemployment, and a decline in labor market participation rate that is "equivalent to 255 million jobs" (ILO, 2020); YLL due to premature deaths; and a decline in life expectancy to inflict a loss of US$10 trillion in future earnings (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%